Hoverflies (Diptera : Syrphidae) as pollinators of sunflowers in the Waterberg region of Limpopo province, South Africa - Weldon, Christopher W. (University of Pretoria, 2023)
Dissertation (MSc (Entomology))--University of Pretoria, 2023.